Identificación de los riesgos laborales en el profesional de enfermería del Hospital Básico Aníbal González Álava de la ciudad de Calceta - Chávez Hidalgo, Rita Karina (2020)
This work proposes improvement actions in the identification of occupational risks to which the nursing professionals of the Aníbal González Álava Basic Hospital in the city of Calceta are exposed, in which nurses have a direct relationship with biological risks, due to constant exposure from the patients. This research integrates a set of methodological tools of a scientific nature based on research that serve as a referential framework. The methodology used allowed to collect information under the established, that is why through the techniques such as the interview, survey and observation, data was collected for the respective tabulation and analysis of the information. The survey was applied to a total of 28 nurses and the interview with the director of the institution where six questions were asked and by which it was announced that the Hospital is not a decentralized unit, it is anchored to District 13D06, it was also indicated that 70% of nursing personnel know occupational health and safety protocols, however, there are workers who are not aware of the dangers to which they are exposed. Based on the problems encountered, a hierarchical matrix was designed that can be used internally as a control tool and actions were proposed to mitigate professional accidents in three stages; the identification of the processes and activities of the nurses, risk map of the work areas and the improvement plan.